(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Cloud computing is a technology offering services in which resources are provisioned on an onneed,pay per use basis through web-based tools and applications, as opposed to a direct connection to aserver. Data sharing is made possible via cloud computing, which can increase the user’s efficiency andoutput. Nonetheless, there are numerous privacy and security flaws in the Cloud that prevent itswidespread use for collaborative purposes. As a result, there is a need for data owners to have some sayover what happens to their data once it has been made available to data consumers, in addition to a needfor their data to remain private secure in the Cloud. Key management, security assaults, data-owneraccess control are three of the most pressing problems with cloud-based information exchange. When itcomes to key management, encryption of data before putting it into the Cloud is essential for keepingsensitive information secret.